Flash spark plasma sintering of magnesium silicide stannide with improved thermoelectric properties. Issue 6 (26th January 2017) - Du, Baoli; Gucci, Francesco; Porwal, Harshit; Grasso, Salvatore; Mahajan, Amit; Reece, Mike J.
Abstract : Flash sintering is capable of rapid densification of thermoelectric materials with optimised microstructure, conductivity, and distribution of surface oxidation. Abstract : Spark plasma sintering has become a routine method for the densification of thermoelectric (TE) materials. However, the impacts and details of direct Joule heating within TE materials have not been fully quantified and clarified. Here we investigated the feasibility of flash-sintering (high heating rate Joule heating) magnesium silicide stannide (MSS) using a spark plasma sintering furnace. A Mg2.1 Si0.487 Sn0.5 Sb0.013 (MSS) green compact was sandwiched between two graphite punches without a die. Then a DC pulse voltage was applied between the punches and the current passed completely though the compact, without any of the current bypassing through a graphite die as occurs with a convectional SPS die–punch system. The direct heating was so efficient that a heating rate of ∼1000 °C was achieved and the sample was fully sintered in less than 45 s. Due to the high local Joule heating at the contacts of the particles, the MgO distribution pattern was modified and optimised, which broke the coated passivation layer on the MSS aggregates. The onset densification temperature was 170 to 350 °C lower than that in convectional SPS (750 °C). Importantly, it was possible to produce dense samples in a wide sintering window of ∼6 s, and the flash-sintering was controllable and repeatable. Flash sintering could open a new way for rapid densification of dense nanostructured and/or textured TE materials with low electrical resistivity by optimising the distribution or removal of the surface oxidation of the powder grains.